Temporal extracellular vesicle protein changes following intraarticular treatment with integrin α10β1-selected mesenchymal stem cells in equine osteoarthritis - Clarke, Emily J.; Johnson, Emily; Caamaño Gutierrez, Eva; Andersen, Camilla; Berg, Lise C.; Jenkins, Rosalind E.; Lindegaard, Casper; Uvebrant, Kristina; Lundgren-Åkerlund, Evy; Turlo, Agnieszka; James, Victoria; Jacobsen, Stine; et al. (Frontiers in Veterinary Science, 2022)
Equine osteoarthritis (OA) is a heterogeneous, degenerative disease of the musculoskeletal system with multifactorial causation, characterised by a joint metabolic imbalance. Extracellular vesicles are nanoparticles involved in intracellular communication. Mesenchymal stem cell (MSC) therapy is a form of regenerative medicine that utilises their properties to repair damaged tissues. Despite its wide use in veterinary practice, the exact mechanism of action of MSCs is not fully understood. The aim of this study was to determine the synovial fluid extracellular vesicle protein cargo following integrin α10β1-selected mesenchymal stem cell (integrin α10-MSC) treatment in an experimental model of equine osteoarthritis with longitudinal sampling. Adipose tissue derived, integrin α10-MSCs were injected intraarticularly in six horses 18 days after experimental induction of OA . Synovial fluid samples were collected at day 0, 18, 21, 28, 35, and 70. Synovial fluid was processed and extracellular vesicles were isolated and characterised. Extracellular vesicle cargo was then analysed using data independent acquisition mass spectrometry proteomics. A total of 442 proteins were identified across all samples, with 48 proteins differentially expressed (FDR≤ 0.05) between sham-operated control joint without MSC treatment and OA joint treated with MSCs. The most significant pathways following functional enrichment analysis of the differentially abundant protein dataset were serine endopeptidase activity (p=0.023), complement activation (classical pathway) (p=0.023), and collagen containing extracellular matrix (p=0.034). Due to the lack of an OA group without MSC treatment, findings cannot be directly correlated to only MSCs. To date this is the first study to quantify the global extracellular vesicle proteome in synovial fluid following MSC treatment of osteoarthritis. Changes in the proteome of the synovial fluid-derived EVs following MSC injection suggest EVs may play a role in mediating the effect of cell therapy through altered joint homeostasis. This is an important step towards understanding the potential therapeutic mechanisms of MSC therapy, ultimately enabling the improvement of therapeutic efficacy.